Urban Violence: critical analysis and limitations of the concept - Saborío, Sebastián (2018)
So far it does not exist a definition of urban violence accepted by the academic community. However, this does not preclude the fact that the concept is abundantly used in social sciences. In most cases, scientific publications use it uncritically as a synonym of crime and homicides. In other cases, some authors propose definitions that do not go beyond a simple description of the characteristics of violence in specific urban settings. However, such descriptions cannot be generalized to other social realities. First, the author’s article explains the importance of verifying the concept’s efficacy through the results of bibliographical analysis; then, it elucidates which are its main limitations and weaknesses. When referring to urban violence, social sciences used to consider mainly those forms of violence that are highly visible and that make possible that a city passed to be identify as violent, reducing people’s perception of safety. The concept’s main problem lies on the fact that it is usually employed to describe the violence of the socially excluded communities that do not have the power to define it. Therefore, its uncritical use can consolidate stigmatized and criminalized depictions of such populations and the territories they reside that can potentially reinforced restrictive and punitive discourses in politics and security.Keywords: limitations; urban violence; visibility.